Food and Nutrition Actions and their Interface with Food Security: a comparison between Brazil and Portugal - Vieira, Viviane (2013)
This paper aims to compare food and nutrition actions related to foodsecurity (FS) in Brazil and Portugal, keeping in mind that several countries have established guidelines to guarantee adequate food. Both nations are experiencing a reduction in fertility rates, increased life expectancy, and a high prevalence of non-communicable diseases. In Brazil, 30.2% of households live in food insecurity; in Portugal, even without estimating food insecurity, 18.0% of its inhabitants are at risk for poverty. The National Food and Nutrition Policy is the current Brazilian document which seeks to ensure universal access to food. Portugal, due to its inclusion in the European Union, is guided by the Second WHO European Action Plan for Food and Nutrition Policy as well as by the Portuguese National Health Plan, which has been updated periodically. Guided by the intersectoral approach, these countries share actions related to FS, such as combating obesity, preventing nutritional deficiences and promoting nutrition education in schools, whereas, specifically in Brazil, some strategies also combat malnutrition and, in Portugal, are linked to industry and the production of safe food. With relation to FS, some distinctions were seen: FS is more widely discussed by Brazilian policies, while this subject is implied in several food and nutrition actions in Portugal. Keywords: Health Public Policy; Food Security; Nutrition Programs; Brazil; Portugal.